2005
DOI: 10.1002/maco.200403821
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of a X80 steel to hydrogen embrittlement

Abstract: The susceptibility to hydrogen of a X80 grade steel produced by a thermo-mechanical control process (TMCP) has been investigated by keeping straining notched specimens under continuous charging conditions. Hydrogen charging was carried out either in synthetic seawater under potentiostatic control at À 1000 mV vs. SCE or in sulphuric acid with an absorption promoter under galvanostatic control at À 5 mA/cm 2 .Results reported in terms of hydrogen effect on the ductility of the steel as a function of both cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…It has been demonstrated [14,31,32] that hydrogen-charging would enhance the anodic dissolution of the steel. Therefore, the size of the semicircle in EIS plots, which is associated with the chargetransfer resistance of corrosion reaction, decreases with the hydrogen-charging current density, as seen in Fig.…”
Section: Effects Of Hydrogen-charging and Stress On Corrosion Of X80 mentioning
confidence: 99%
“…It has been demonstrated [14,31,32] that hydrogen-charging would enhance the anodic dissolution of the steel. Therefore, the size of the semicircle in EIS plots, which is associated with the chargetransfer resistance of corrosion reaction, decreases with the hydrogen-charging current density, as seen in Fig.…”
Section: Effects Of Hydrogen-charging and Stress On Corrosion Of X80 mentioning
confidence: 99%
“…In order to reduce the cost of production of pipelines, directly related to the quantity of metal needed, high strength steels are used such as X80 for natural gas. However, previous workers have shown that many high strength steels are susceptible to hydrogen embrittlement, inducing degradations of the mechanical properties [1][2][3]. The purpose of this study is both to assess the specific resistance of X80 to hydrogen embrittlement and to contribute to an improvement of the understanding of hydrogen effect on high strength steels.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a defect (hole, notch) on specimen increases the stressconcentration and modifies the hydrostatic stress in the process zone ahead of the defect, influencing locally the hydrogen content [9,10]. It also changes the local loading.…”
Section: Fatigue Crack Initiationmentioning
confidence: 97%